Estimating the burden of care for oral potentially malignant disorders and oral cancer in Brazilian dental practice - de Paiva, João Paulo Gonçalves; Jorge, Jacks; Dos Santos, Erison Santana; Migowski, Arn; Cohen-Goldemberg, Daniel; Kowalski, Luiz Paulo; Brandão, Thaís Bianca; Ribeiro, Ana Carolina Prado; Lopes, Marcio Ajudarte; Vargas, Pablo Agustin; da Silva, Eurípides Alves [UNESP]; Warnakulasuriya, Saman; et al. (My University, 2024)
Background: Oral cancer (OC) and oral potentially malignant disorders (OPMD) pose significant challenges to public health in Brazil. This study aimed to estimate the prevalence of oral cancer (OC) and oral potentially malignant disorders (OPMD) among patients who would be treated by Brazilian dentists during their careers. Material and Methods: Data on the number of dentists in Brazil were extracted from the 2022 census data, while incidence rates for OC cases were sourced from the Brazilian National Cancer Institute (INCA). Population estimates for Brazil and data on dental check-up rates were obtained from relevant national sources. Results: Our analysis indicates that a general dentist in Brazil can expect to encounter on average two to three OC patients and on average 675 patients with OPMDs over a 35-year career. Regional disparities were observed, with certain regions showing higher than the average number of encounters due to low density of dentists in some rural districts. Conclusions: Brazilian dentists are likely to confront a substantial number of OC and OPMD cases during their professional tenure, emphasizing the need for public health policies aimed at enhancing dental surgeons' education in oral cancer prevention and early detection.
Keywords: burden estimation; dentistry; Oral cancer; potentially malignant disorders; public health